Recent advances in Big Data Analytics, Internet of Things and Machine Learning - Martis, Roshan Joy; Gurupur, Varadraj Prabhu; Lin, Hong; Islam, Aminul; Fernandes, Steven Lawrence (Future generation computer systems, 2018)
Big data analytics, Internet of Things, and machine learning are some of the rising areas of science and technology forming the next generation of artificial intelligence-based computing systems. It is also important to note that this aforementioned emerging field is diverse and in some strange ways both transformative and transdisciplinary in nature. This transformative and transdisciplinary nature of this field enables it to grow both in terms of its theoretical foundations and applications. In this special issue we focus on some advanced research projects in these areas that are transformative and transdisciplinary in nature. The projects and experiments discussed in this special issue constitute the advancement in synthesis of decision support systems that aid further advancement of healthcare delivery, diagnosing diseases, and analysis of behavioral science.